2009
DOI: 10.4049/jimmunol.0900879
|View full text |Cite
|
Sign up to set email alerts
|

Complement Protease MASP-1 Activates Human Endothelial Cells: PAR4 Activation Is a Link between Complement and Endothelial Function

Abstract: Activation of the complement system can induce and enhance inflammatory reaction. Mannose-binding lectin-associated serine protease-1 (MASP-1) is an abundant protease of the complement lectin pathway; however, its physiological function is unclear. In this study, we demonstrate for the first time that MASP-1 is able to activate Ca2+ signaling, NF-κB, and p38 MAPK pathways in cultured HUVECs. Activation was initiated by MASP-1 only; the related protease, MASP-2, had no such effect. The phenomenon was dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(92 citation statements)
references
References 51 publications
(44 reference statements)
6
85
0
1
Order By: Relevance
“…It has been demonstrated that MASP-1 induces p38- mitogen-activated protein kinases (MAPK) activation, NFkappaB signaling and Ca 2+ mobilization in HUVECs, inducing IL-6 and IL-8 production (Jani et al, 2014) as well as E-selectin expression (Dobó et al, 2014). MASP-1, like thrombin, also activates endothelial cells directly by cleaving the protease activated receptors (PARs; Megyeri et al, 2009). Other complement components have been demonstrated to interact with endothelial cells and promote vascular toxicity.…”
Section: Sources and Compartments Of Activationmentioning
confidence: 99%
“…It has been demonstrated that MASP-1 induces p38- mitogen-activated protein kinases (MAPK) activation, NFkappaB signaling and Ca 2+ mobilization in HUVECs, inducing IL-6 and IL-8 production (Jani et al, 2014) as well as E-selectin expression (Dobó et al, 2014). MASP-1, like thrombin, also activates endothelial cells directly by cleaving the protease activated receptors (PARs; Megyeri et al, 2009). Other complement components have been demonstrated to interact with endothelial cells and promote vascular toxicity.…”
Section: Sources and Compartments Of Activationmentioning
confidence: 99%
“…We now suggest that crosstalk of coagulation enzymes with other proteolytic cascades, like those of the complement (Oikonomopoulou et al, 2012) and the KLK system (Blaber et al, 2010), can similarly play an amplification role to activate PAR signaling. In particular, the cross-relationship between the MASP-1 complement proteinase and endothelium-dependent PAR4 signaling supports this hypothesis (Megyeri et al, 2009). This kind of 'proteolytic cascade'-driven PAR signaling is likely to play a role not only in the inflammatory response, but also in the setting of tumorigenesis, as outlined in the following sections.…”
Section: Proteolytic Cascades Klks and The Innate Immune Responsementioning
confidence: 87%
“…All three complement pathways have been implicated in EC activation (Heinen et al 2007;Megyeri et al 2009;Zhang et al 2007). The products of the terminal complement pathway (C5a and C5b-9) have direct effects on ECs.…”
Section: Role Of Complement In Ec Homeostasis and Activationmentioning
confidence: 97%